A Comparison of Post-operative Pain After Septoplasty with and without Nasal Packing in Patients Presenting with Nasal Septal Deformities (Journal of Fatima Jinnah Medical University, 2018)
Objective: Objective of this study was to compare the post-operative pain after septoplasty with and without nasal packing in patients presenting with nasal septal deformity (NSD).Methodology: This randomized controlled trial was conducted at Department of Otolaryngology Sir Ganga Ram Hospital, Lahore for a duration of one year in the year 2014. One hundred cases of nasal septal deformity were included in the study through Non-Probability Purposive Sampling. The patients were randomly divided into two groups. In group A, 50 patients underwent septoplasty with nasal packing while in group B, septoplasty without nasal packing was done in 50 patients. Postoperative severe pain (visual analogue scale VAS>7) was noted. The collected data was analysed statistically by using SPSS version 16. Both groups were compared for post-operative pain by using chi-square test. P-value
Keywords: Nasal septal deformity, septoplasty, nasal packing, pain, visual analogue scale.